Lexicology, semantics, and lexicography : selected papers from the fourth G.L. Brook Symposium, Manchester, August 1998 - G.L. Brook Symposium 1998 : Manchester, England); Coleman, Julie; Kay, Christian (Amsterdam ; Philadelphia : J. Benjamins, 2000)
The papers in this volume show the range and direction of current work in historical semantics and word-studies. There is a strong focus throughout on semantic change and lexical innovation, interpreted within a sociolinguistic, cultural or textual context. Many of the papers draw on the remarkable range of electronic resources now available to historical linguists, notably corpora, dictionaries, bibliographies and thesauruses, and show the effects that these have had in stimulating new lines of research or the re-interpretation of previous conclusions. Cognitive semantics, and especially prot.
LEXICOLOGY, SEMANTICS AND LEXICOGRAPHY; Editorial page; Title page; LCC Data; Contents; Introduction; G L Brook: 1910-1987; List of Contributors; Lexical Gaps, Cognition and Linguistic Change; Folk-Etymology: Haphazard Perversion or Shrewd Analogy?; Mechanisms of Semantic Change in Nouns of Cognition: a General Model?; Historical Semantics and Historical Lexicography: will the twain ever meet?; Strange Linguists: The Cant and Slang Dictionary Tradition; Lexical Choices in an Early Galilean Translation; Grund to Hrof: Aspects of the Old English Semantics of Building and Architecture.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Lexicology -- Congresses; Semantics -- Congresses; Lexicography -- Congresses; Lexicologie -- Congrès.; Sémantique -- Congrès.; Lexicographie -- Congrès.; Lexicography; Lexicology; Semantics; Historische Lexikografie; Historische Lexikologie; Historische Semantik; Lexicologie; Lexicografie; Semantiek; Manchester <1998>; Englisch; Conference papers and proceedings